Effects of polymer micro-structures on the thermo-optical properties of a flexible soft-mater film based on liquid crystals / polymer composite. (20th June 2018) - Liang, Xiao; Chen, Mei; Chen, Gang; Li, Chunxin; Han, Cheng; Zhang, Juanrong; Zhang, Jiazhen; Zhang, Lanying; Yang, Huai
Abstract: Organic thermochromic materials (e.g. hydrogels, conjugated polymers) are promising candidates for applications, such as energy-saving windows, temperature indicators and decoration items. Compared with the traditional thermochromic materials, liquid crystals (LC)/polymer composites are more advantageous in large-area manufacturing and facile processing. However, the effects of polymer micro-structures on the thermal-optical properties of these LC based thermochromic materials, which is crucial for both high mechanical strength and excellent optical performance, still remain unclear. To this end, herein a systematic investigation on the relationships between the polymer micro-frameworks and the thermal-optical properties is conducted for the first time based on a soft-matter composite of polymer/temperature-responsive liquid crystals, and finally the mechanical strength of the composite material is enhanced to be as high as ∼110 N/cm 2, without compromising the modulation contrast, which enlightens new insights in regulating the optical-properties of novel soft-matter composite materials towards practical applications. Graphical abstract: Image 1 Highlights: Effects of microstructures on the thermo-optical properties of a liquid crystal/polymer composite system were investigated. The contents of the polymeric syrup and the curing temperature have great influences on the polymer microstructures. The relationships between the thermal-optical properties and the different polymer microstructures were established. Curing temperature is crucial for a composite film with both good thermo-optical properties and high mechanical strength.